Handbook on prisons and jails - Rudes, Danielle Sheldon; Armstrong, Gaylene Styve; Kras, Kimberly Raye; Carter, TaLisa J. (The ASC Division on Corrections & Sentencing handbook series, 2024)
"The Handbook on Prisons and Jails brings together the some of the brightest scholars and thinkers in the field to offer a wide range of perspectives for understanding the experiences of persons incarcerated or working/volunteering within carceral institutions"--